Cidades inteligentes e as praças centrais urbanas: uma análise em São Luís (MA) - SILVA, Lorena Victoria Pereira da (2024)
The main objective of this work was to analyze, from the perspective of the ergonomics of the built environment, the current panorama and future smart city initiatives applied or idealized to urban central squares in the city of São Luís (MA). The importance of this research is justified by the need to turn attention to public spaces that have long had their functions linked to the meeting and sociability of citizens, and which have the potential to reinvigorate the quality of urban life: public squares. To analyze these physical spaces, the ergonomics of the built environment was used, which addresses the interaction of human beings (in this case, the citizens of São Luís) with the physical spaces (with the focus in this research being the central squares of São Luís) that accompanied the entire development of the city, since its conception. The theme of smart cities entered the work based on the need to propose a vision focused on the future of these spaces, considering that São Luís has taken steps to insert itself into the Brazilian smart cities scenario. To achieve the proposed objective, the study used the following methodological procedures: a bibliographical research, to compose the theoretical framework; a documentary research; and field research, using different techniques for data collection (opinion survey, SWOT matrix, questionnaire). As a result, a material was produced that can assist in urban planning processes aimed at the squares of the capital of Maranhão.